Accepted level of risk of doping use in the view of young athletes - Mroczkowska, H. (Biology of Sport, 2011)
The paper is a continuation of studies aimed at verifying the hypothesis from decision theory stating that the risk in action is the greatest when the probability of loss is high, and the higher the value attached to that which is lost as a consequence of this action. Students of the Sport Championship School (n = 89) from fencing, track and field, martial arts and football classes took part in the studies. The age of the study participants was in the range 16-18 years. The experimental technique "Perception of risk of doping" (author: H. Mroczkowska) was used to help to determine the individual ranking of possible losses of valued goods as a consequence of doping use (loss of health; loss of medal; loss of physical attractiveness; loss of emotional balance; loss of material reward; loss of respect from others). It turns out that the hierarchy of the values that may be lost as a consequence of doping variously influences the assessment of the real and subjective risk and concerns various areas of evaluation. The assessment of the objective risk depends more on the rank of what may be lost (health) than on what may be gained (medals). Moreover, direct external sanctions are not perceived as more probable than remote personal consequences (psychophysical health). In the real situation of decision making about doping, the internalized hierarchy of values has no greater significance; in the real danger of a doping disclosure, everything that can be lost turns out to be equally valuable.